VALIDITY AND RELIABILITY OF A DIGITAL INCLINOMETER IN ANKLE JOINT POSITION SENSE ASSESSMENT - THARAWADEEPIMUK, Kittichai; LIMROONGREUNGRAT, Weerawat; PILANTHANANOND, Metaneeya; NANBANCHA, Ampika (Journal of Sports Science and Technology, 2022)
The ankle joint position sense is crucial for human movements. To date, several measurement tools have been used in assessing joint position sense. However, they are mostly high-costly and involve a complex system demonstrating a major limitation to be used in the field. This study employed an affordable and portable digital inclinometer to examine the angle of ankle movement in joint position sense testing. This study aimed to evaluate the criterion validity of the digital inclinometer, as well as intra- and inter-rater reliability of ankle joint position sense using a digital inclinometer. Twenty-one participants (23.86+3.98 years) without a history of lower limb injury were recruited. The ankle joint position sense was evaluated by two testers using a digital inclinometer that was attached to right dorsum of the foot to detect angle changes. The digital inclinometer’s criterion validity was examined by comparing the recorded degree of movement using an isokinetic dynamometer and a digital inclinometer. Dorsiflexion and plantarflexion angles were recorded by the digital inclinometer in the right ankle and used for intra- and inter-rater reliability analysis. Intraclass correlation coefficient (ICC) models were used to determine reliability. The Bland-Altman plots demonstrated the point distribution within the interval to validate the digital inclinometer validity. The intra-rater reliability of the joint position sense test exhibited moderate in 1st rater (ICC 0.525-0.610), and poor in 2nd rater (ICC 0.398-0.478). Inter-rater reliability was poor agreement between two raters (ICC 0.43-0.48). The digital inclinometer can be considered as a valid, accurate, and portable tool for measuring the ankle range of motion, and ankle joint position sense in an individual rater. However, the multiple-rater reliability was poor to moderate. This low inter-rater reliability may be due to inaccurate placement of the inclinometer on the foot or a different level in the testing experience. (Journal of Sports Science and Technology 2022; 2222 (2): 80-90)) (Received: 7 July 2022, Revised: 3 October 2022, Accepted: 12 October 2022) *Corresponding Author: Ampika Nanbancha College of Sports Science and Technology, Mahidol University, Nakhon Pathom, Thailand 73170 E-mail: ampika.nan@mahidol.edu